PERANAN SUPERVISI PENDIDIKAN KEPALA SEKOLAH TERHADAP KOMPETENSI PROFESIONAL GURU - Kaderiah, Kaderiah (Universitas Negeri Makassar, 2023)
Abstract: This research aims to (1) To know How Supervising Principal education at SMPN Makassar (2) to determine how competence profesioanal teacher At SMPN Makassar. (3) to determine how the role of supervising the competence profesioanal education teacher at SMPN Makassar. This research is a qualitative descriptive study. Technique data collecting by interview, documentation and observation. Once the sample population of this study is the Principal and Teacher SMPN Makassar. The results showed that educational supervision Headmaster of SMPN Makassar had behaved correctly, where the task in question is his duty as an educator, manager, administrator, supervisor, leader, innovator and entrepreneur has been going well so as to create a professional teacher and have an impact on the increase student achievement in school.